Anti-Infection of Oral Microorganisms from Herbal Medicine of Piper crocatum Ruiz & Pav - Kurnia D; Lestari S; Mayanti T; Gartika M; Nurdin D (Drug Design, Development and Therapy, 2024)
Dikdik Kurnia,1 Seftiana Lestari,1 Tri Mayanti,1 Meirina Gartika,2 Denny Nurdin3 1Department of Chemistry, Faculty of Mathematics and Natural Science, Universitas Padjadjaran, Sumedang, Indonesia; 2Department of Pediatric Dentistry, Faculty of Medicine, University of Padjadjaran, Bandung, Indonesia; 3Departement of Conservative Dentistry, Faculty of Dentistry, Universitas Padjadjaran, Bandung, IndonesiaCorrespondence: Dikdik Kurnia, Email dikdik.kurnia@unpad.ac.idAbstract: The WHO Global Status Report on Oral Health 2022 reveals that oral diseases caused by infection with oral pathogenic microorganisms affect nearly 3.5 billion people worldwide. Oral health problems are caused by the presence of S. mutans, S. sanguinis, E. faecalis and C. albicans in the oral cavity. Synthetic anti-infective drugs have been widely used to treat oral infections, but have been reported to cause side effects and resistance. Various strategies have been implemented to overcome this problem. Synthetic anti-infective drugs have been widely used to treat oral infections, but they have been reported to cause side effects and resistance. Therefore, it is important to look for safe anti-infective alternatives. Ethnobotanical and ethnopharmacological studies suggest that Red Betel leaf (Piper crocatum Ruiz & Pav) could be a potential source of oral anti-infectives. This review aims to discuss the pathogenesis mechanism of several microorganisms that play an important role in causing health problems, the mechanism of action of synthetic oral anti-infective drugs in inhibiting microbial growth in the oral cavity, and the potential of red betel leaf (Piper crocatum Ruiz & Pav) as an herbal oral anti-infective drug. This study emphasises the importance of researching natural components as an alternative treatment for oral infections that is more effective and can meet global needs.Keywords: Piper crocatum, anti-infection, antibacterial, antifungal, oral pathogen